STUDI KESESUAIAN KUALITAS AIR UNTUK BUDIDAYA IKAN LELE DUMBO (Clarias gariepinus) DI KAMPUNG LAUK KABUPATEN BANDUNG - Perdana Putra Kelana; Ujang Subhan; Ibnu Bangkit Biosina Suryadi; Rangga Bayu Kusuma Haris (Aurelia Journal, 2021)
Kampung lauk in Bandung district is one of the efforts to increase the production of catfish (Clarias gariepinus). The purpose of this study was to determine the suitability of water quality for catfish cultivation in Bandung district. The Method used in this study was a survey method with purposive sampling technique to determine the point of observation and water sampling. This study was carried out in 3 stations which were potential locations for the lauk village with 2 sampling points at each station. Parameters observed were temperature, dissolved oxygen, pH and ammonia in accordance with the parameters listed in SNI 01-6484.5: 2002 Catfish (Clarias gariepinus) Rearing Class. Based on observations, the average value of all parameters at all stations is in accordance with SNI 01-6484.5: 2002, except for pH at station 2. Based on this, stations 1 and 3 are suitable for catfish cultivation, station 2 is not suitable.